The complex relationship between students’ critical thinking and epistemological beliefs in the context of problem solving - Hyytinen, Heidi; Holma, Katariina; Toom, Auli; Shavelson, Richard J.; Lindblom-Ylänne, Sari (Frontline Learning Research, 2014)
The study utilized a multi-method approach to explore the connection between critical thinking and epistemological beliefs in a specific problem-solving situation. Data drawn from a sample of ten third-year bioscience students were collected using a combination of a cognitive lab and a performance task from the Collegiate Learning Assessment (CLA). The cognitive-lab data were analysed using thematic analysis. The findings showed that students’ epistemological beliefs were interwoven into their critical thinking: students used critical thinking as a tool (1) for enhancing understanding and (2) for determining truth or falsehood. Based on this classification, students could be placed in one of two qualitative profiles, either (1) thorough processing or (2) superficial processing. The results indicated that students who showed superficial processing palmed off justification for knowing on authoritative figures. In contrast to previous studies these students did not consider knowledge to be absolutely certain or unquestionable. The findings also show that students with thorough processing believed knowledge to be tentative and fallible, but did not share the relativist view of knowledge where any claim counts because all knowledge is relative. All ten students shared a fallibilist view of knowledge.